Transport of vanadium (V) in saturated porous media: effects of pH, ionic-strength and clay mineral. Issue 1 (1st October 2016) - Wang, Yulu; Yin, Xianqiang; Sun, Huimin; Wang, Changzhao
Abstract: Vanadium, a hazardous pollutant, has been frequently detected in soil and groundwater, however, its transport behavior in porous media were not clearly understood. In this study, the effects of solution pH, ionic strength (IS) and the effect of clay mineral on the transport of vanadium in saturated porous media were investigated. Laboratory experiments using a series of columns packed with quartz sand were carried out to explore the retention and transport of vanadium with a range of ionic-strength (0.001–0.1 M) and pH (4–8) and two different types of clay minerals montmorillonite and kaolinite. Results of the breakthrough experiments showed that vanadium was highly mobile in the saturated porous media. The increase in pH rendered a higher transport of vanadium in saturated porous media. The study also indicated an easier transfer of vanadium with an increase in IS. Montmorillonite enhanced the mobility of vanadium in the column when compared to kaolinite. A mathematical model based on advection-dispersion equation coupled with equilibrium and kinetic reactions was used to describe the retention and transport of vanadium in the columns very well.